Customer Experience, Customer Service Quality, Customer Perceived Value, and Customer Satisfaction As Impact on Cinema XXI Customer Loyalty in Bandung City - Rifa’atul Mahmudah; Dedi Iskamto (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study was to determine how significant the influence of customer experience and customer service quality on customer loyalty is through customer perceived value and customer satisfaction at Cinema XXI in Bandung City, West Java. The quantitative method is the method used in this research. The sample size was taken from 384 people based on the Coacran formula from an unknown population. Purposive non-probability with data collection through questionnaires measured on a Likert scale is the technique used in sampling. Smart PLS software version 4.0.9.8 using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method is the tool used in this study. The test results show that all independent variables, namely Customer experience and Customer service quality, through intervening variables, namely Customer perceived value and Customer Satisfaction, significantly affect Customer Loyalty at Cinema XXI in Bandung City.